Depositional environment analysis of the Pennslyvanian, mid-continent Tonkawa sandstone. - Cashman, Amanda L. (Kansas State University, 2011)
Hydrocarbon production throughout the continental United States has declined in past decades. New interpretations together with advanced recovery techniques can increase production in older fields. Re-examining these types of underdeveloped resources is a simple and cost effective tool that can be readily used to increase hydrocarbon production throughout the mid-continent. Pennsylvanian sandstones throughout Oklahoma and Kansas are known for their excellent reservoir qualities. The focus of this study is the upper Pennsylvanian Tonkawa Formation, a sandstone dominated unit. The Tonkawa has been informally correlated to both the Stalnaker and Tonganoxie sandstones in Kansas. Previous publications do not present a unified understanding of the depositional environments that are seen across state borders. The interpretations vary from fluvio-deltaic to marine environments. A cohesive interpretation is necessary to understand paleo-processes and efficiently exploit the reservoir for hydrocarbons. The study presents a regional analysis covering an eleven county area in northwest Oklahoma. Analysis of core and well log data is used to determine the range of depositional environments of the Tonkawa sandstone. Sedimentary structures, mineral assemblages, and lithologies of selected cores are described and correlated with well log data. With this data, structural isopach maps are constructed using Petra software. Earlier interpretations have relied primarily on well log data, focusing on core data rather than geophysical logs, allowing for a more detailed and accurate interpretation. Analysis of transitional sedimentary sequences, such as the Tonkawa, can be applied to sandstones deposited in similar environments throughout the mid-continent.
Keywords: Tonkawa sandstone; Geology (0372)